Symmetry operators of the two-component Gross—Pitaevskii equation with a Manakov-type nonlocal nonlinearity; Journal of Physics: Conference Series; Vol. 670, conf. 1 : XXIII International Conference on Integrable Systems and Quantum Symmetries (ISQS-23) - Shapovalov A. V. Aleksandr Vasilyevich (2016, 2016)
Title screen